The Effect of Chitosan Priming on Germination and Biochemical Characteristics of Black Seed (Nigella sativa L.) under Cadmium Stress - Ellahe Arab; Leila Ahangar; Abbas Biabani (پژوهشنامه اصلاح گیاهان زراعی)
Extended Abstract Background: Black seed (Nigella sativa L.) from the Ranunculaceae family is one of the natural useful antioxidants, and the oil prepared from its seeds has various medicinal properties, including anti-cancer, anti-microbial, anti-hypertensive, anti-diabetic and increased immunity has been reported. Nigella sativa, like other plants, is constantly exposed to abiotic or biotic stresses. The main abiotic stresses that plants are exposed to include extreme temperature, drought, high salinity and heavy metals. Environmental pollution caused by heavy metals is increasing. Among heavy metals, cadmium is one of the most toxic elements for living organisms, which has received much attention due to its increase in the environment in recent decades. This element is toxic to most plants even in very low concentrations, while in concentrations higher than five to ten micrograms per gram of dry leaf weight, it can lead to the death of the plant. The presence of this element in the growth environment of plants causes a lot of poisoning, including disruption of water-plant relations, disruption of chlorophyll biosynthesis and formation of free ions. Therefore, it is necessary to adopt appropriate environmental methods to reduce or eliminate the negative and irreparable effects of this metal in agriculture. Seed priming is known to be an effective method to improve plant performance by increasing plant tolerance to stress. One of the types of priming methods is the use of chemicals such as chitosan. Chitosan is a non-toxic and environmentally adaptive substance that is very important due to its antioxidant activity in dealing with oxidative damage resulting from environmental stress. Therefore, in this study, the effect of chitosan priming on reducing the harmful effects of cadmium on germination and biochemical characteristics of black seed was investigated. Methods: In this study, in order to investigate the effect of chitosan priming on cadmium chloride stress on the germination and biochemical characteristics of Nigella sativa, the experiment was carried out as a factorial design based on completely randomized design with 4 replications in sterile petri dishes in the laboratories of Gonbadkavos Agricultural University in 2023. For seed priming with different concentrations of chitosan (0.2, 0.4, 0.6, 1.0%), the seeds were immersed in the desired solutions for 3 hours under dark conditions and after drying, they were placed in Petri dishes on Whatman paper bed. Then 5 ml of solutions prepared with different concentrations of cadmium chloride (control, 1000, 750, 500, 250 μmol) were added to them. Distilled water was used for control treatment. Finally, the samples were placed for 10 days in the germinator in dark conditions with a temperature of 25±1 oC. At the end of the experiment, the characteristics of germination percentage, germination rate, seedling vigor index, root and shoot length were measured. Then the biochemical traits of seedlings such as catalase, peroxidase, phenol, soluble sugar and proline were measured after 14 days. Statistical analysis of data was done using SAS 9.1 and MSTAT-C software. Results: The results of analysis of variance indicated the significant simple effects of priming with chitosan and cadmium stress on all investigated traits. Also, the interaction effects of priming × cadmium stress were also significant for all traits at the 1% level. The comparison of average data showed that with the increase of cadmium concentration, germination rate and percentage, radicle length and seedling vigor index decreased significantly, so that the highest amount of these traits was in the control and 250 μmol cadmium and the lowest amount of these traits was observed at a concentration of 1000 μmol cadmium. The external application of chitosan in the form of priming improved germination traits, root and shoot length and seedling vigor index in 0.2 and 0.4% chitosan treatments compared to the control, while with the increase in the percentage of chitosan (0.8 and 1 percent) the amount of these traits decreased significantly. The results of the comparison of average traits under the interaction of chitosan ×cadmium showed that seed priming with chitosan was able to reduce the negative effects of cadmium chloride stress on the traits of percentage germination, root and shoot length and seedling vigor index. Thus, the highest amount of these traits was observed in the treatment of 0.2 and 0.4% chitosan and 250 and 500 μmol cadmium stress. Also, the results of the present study showed that increasing the concentration of cadmium chloride causes an increase in the activity of antioxidant enzymes such as catalase and peroxidase and non-enzymatic antioxidants such as proline and phenol. So that peroxidase enzyme at the treatment of 750 μM of cadmium (0.0053 μmol per gram of fresh tissue) with an increase of 178.2% compared to the control and phenol in the treatment of 1000 μM of cadmium (3.2 mg/g of extract) with an increase of 211.7 % compared to the control showed the highest level of activity. Also, the use of seed priming technique with chitosan could significantly increase the content of these proteins in plants under cadmium stress. So that, the highest amount of peroxidase enzyme is observed in the treatment of 500 μM cadmium in the priming treatment with 0.4% chitosan (0.0083 μmol Bergam of fresh tissue) and in the tratment of 750 μM cadmium chloride in the priming treatment 0.2% chitosan (0.0082 μmol Bergam) fresh tissue). That this amount was about 64 and 57.6% more than their controls, respectively. Conclusion: The results of this research showed that cadmium stress leads to a decrease in germination characteristics and weakens the plant's defense system. To deal with these changes and reduce the adverse effects of the produced ROS, the plant increased the activity of antioxidant enzymes, but the adverse effects of cadmium had an inhibitory effect on these changes. Conversely, the use of chitosan in the form of priming prevented the harmful effects of cadmium and increased the activity of antioxidant enzymes and protected the germination process against the toxicity of this heavy metal. Although the application of chitosan up to 0.6% improved these mechanisms, its beneficial effects decreased with the increase in the concentration of this substance. Based on the results of the present study, it can be stated that the application of chitosan caused the activation of some biochemical and physiological mechanisms in the black seed plant under cadmium stress. Therefore, seed priming with chitosan can be suggested as an effective strategy to increase Nigella sativa tolerance to cadmium stress.